A Chance to Defend Regional Heads in The Procedure of Regional Head Dismissal as A Manifestation of The Proportionality Principle - Aris, Mohammad Syaiful; Fauzurrahman, Iqbal; Abrianto, Bagus Oktafian; Nugraha, Xavier; Felicia, Stefania Arshanty (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
The existence of regional autonomy in Indonesia is implemented through regional leaders who have the authority to run local government. When carrying out their duties, regional leaders are supervised by other state institutions as a form of checks and balances in government power. Hence, the procedure to dismiss regional leaders regulates to involve the Regional People's Representative Assembly, the Supreme Court, and the President through the Minister of Home Affairs as a form of right to dismiss. However, the existence of the proportionality principle in the procedure to dismiss regional leaders, through the right given to regional leaders to defend themselves, has yet to be regulated in the law. This article talks about two things: first, the procedure to dismiss regional leaders, and second, the legal consequences and the position of a chance to summon regional leaders to explain and defend themselves in the procedure to dismiss regional leaders. This article aims to find the importance of proportionality principles in the procedure to dismiss regional leaders. The method used in this article is legal research, with statutes, conceptual, and case approaches. The results of this research show that although the procedure to dismiss regional leaders has been regulated in law, applying the proportionality principle only exists in jurisprudences. Hence, an ius constituendum is needed to determine legal consequences and certainty regarding the procedure to dismiss regional leaders.